A Study on Scour Failure at Bridge Foundation (University of Khartoum Engineering Journal, 2022)
The success of a bridge relies on proper design and construction of its foundations. A Literature concerning water scouring atbridge foundation and some cases of bridge failure were intensively reviewed. Two global cases and a local case of foundation failurecaused collapse of the bridge structure were selected for this study. The study was concentrated on Manshia Bridge in Khartoum. Theinvestigation involved field survey and laboratory testing on this project to examine the existing foundation conditions. The easternabutment investigated experienced sever failures in forms of excessive scouring and settlement in the embankment and the foundationpiles surrounded by water. The causes of these failures were found mainly linked to the high scouring rate of water lead to washout the soil from the embankment of the abutment and the foundation piles. The foundation design mistakes, poor construction, inadequate abutment protection and lack of maintenance were detected as the main cause of the bridge failure. To protect abutment against scouring problem, it is recommended to use rock protection for the embankment and river bed around the abutment.